Toward a Unified School Performance Management Theory: Integrating Stakeholder Engagement, Leadership, Resources, Teacher Efficacy, and Job Satisfaction - Carmelotes, Ariel (JPAIR Institutional Research, 2026)
School performance remains a central concern in educational management, especially in contexts where access, quality, resilience, and efficiency are unevenly distributed. This study develops a management-oriented theory of school performance by integrating five core determinants: stakeholder engagement, supervisory style, resource management, teacher efficacy, and job satisfaction. Drawing on global and local literature published between 2020-2025, the review shows that these determinants influence outcomes only when mediated by trust, communication, equity, transparency, instructional quality, retention, and classroom climate. Stakeholder engagement fosters accountability through dialogue and trust; supervisory style shapes organizational culture; resource management drives performance when equity and transparency are ensured; and teacher efficacy and job satisfaction strengthen instructional quality and retention. Interaction effects, such as engagement combined with supportive supervision or resource equity paired with teacher satisfaction, further magnify outcomes, while socio-economic context moderates their strength. Collectively, the evidence supports a Unified School Performance Management Theory that positions schools as complex systems where managerial, relational, and psychological processes interact to sustain performance. Practically, this framework guides school leaders in sequencing interventions - prioritizing trust-building, coaching supervision, equitable resource allocation, and teacher support - to improve continuity, accountability, and innovation in teaching.